2021
DOI: 10.4269/ajtmh.20-0532
|View full text |Cite
|
Sign up to set email alerts
|

Social and Environmental Determinants of Community-Acquired Antimicrobial-Resistant Escherichia coli in Children Living in Semirural Communities of Quito, Ecuador

Abstract: Extended-spectrum beta-lactamase-producing Enterobacteriaceae (ESBL), a family of bacteria that includes Escherichia coli, have emerged as a global health threat. This study examined risks associated with carriage of third-generation cephalosporin-resistant (3GC-R) E. coli, including ESBL-producing, multidrug-resistant, and extensively drug-resistant (XDR) strains in children living in semirural parishes of Quito, Ecuador. We conducted a longitudinal study with two cycles of sampling (N = 374, N = 366) that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 50 publications
0
12
1
Order By: Relevance
“…Food animals at households with more than 5 people also had increased odds of ESBL-producing E. coli carriage in this study. We have not observed previous reports of such associations in food animals, though in humans, AMR has been linked to household crowding [96], and crowding of 2.5-8 people per room in this study's region has been previously weakly associated with increased though insignificant odds of ESBL-producing, 3GCR-MDR, and 3GCR-XDR E. coli in humans [62]. Similar pathways related to household crowding, as well as the potential for an increased number of food animal and human exposures in households with more people, may drive some fraction of the resistance observed in both food animals and humans in this setting.…”
Section: Plos Global Public Healthcontrasting
confidence: 87%
See 1 more Smart Citation
“…Food animals at households with more than 5 people also had increased odds of ESBL-producing E. coli carriage in this study. We have not observed previous reports of such associations in food animals, though in humans, AMR has been linked to household crowding [96], and crowding of 2.5-8 people per room in this study's region has been previously weakly associated with increased though insignificant odds of ESBL-producing, 3GCR-MDR, and 3GCR-XDR E. coli in humans [62]. Similar pathways related to household crowding, as well as the potential for an increased number of food animal and human exposures in households with more people, may drive some fraction of the resistance observed in both food animals and humans in this setting.…”
Section: Plos Global Public Healthcontrasting
confidence: 87%
“…In communities outside of Quito, horizontal transfer of AMR genes and mobile genetic elements is thought to play a dominant role in ESBL-producing E. coli transmission between domestic animals and humans [13,61]. While risk factors for colonization with ESBL-producing E. coli have been identified for children in the region, specific household characteristics and antibiotic knowledge, attitudes, and practices (KAP) contributing to domestic animal colonization with 3GCR and ESBL-producing E. coli have yet to be explored [62]. Identifying such risk factors could help direct future mitigation and prevention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…One paper reported that, compared to the head of a family being a manager, pregnant women whose head of a family was unemployed, unskilled, semi-skilled, or a non-manual employee had a higher risk of intestinal colonization with extended-spectrum beta-lactamase (ESBL)-producing Enterobacterales (14). Twelve comparisons from eight studies did not find a statistically significant association between participants' education status and their risk of colonization/infection with an outcome of interest (9,10,12,(14)(15)(16)18,19).…”
Section: Educationmentioning
confidence: 99%
“…Eighteen studies reported outcomes of interest by participants' income status (9)(10)(11)(12)15,16,18,(20)(21)(22)(23)25,31,(34)(35)(36)(37)(38) (Table 4). Among the 36 comparisons for which authors statistically evaluated the association between participants' income and an outcome of interest, approximately nine comparisons demonstrated an association between low-income levels and elevated risk of colonization/infection with priority pathogens, regardless of their susceptibility to antibiotics.…”
Section: Incomementioning
confidence: 99%
“…Exposure to animal feces can also increase the risk of diarrhea (29)(30)(31). Exposure and risk assessments and epidemiological studies in LMICs have focused on exposures to feces or fecal pathogens, broadly; few epidemiological studies have assessed exposures and risk factors for antibioticresistant and ESBL-E infections among children in LMICs (32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%